Development of bread wheat (Triticum aestivum L) variety HD3411 following marker-assisted backcross breeding for drought tolerance - Kumar, Prashanth K. C.; Bellundagi, Amasiddha; Krishna, Hari; Mallikarjuna, Mallana Gowdra; Thimmappa, Ramya K.; Rai, Neha; Shashikumara, P.; Sinha, Nivedita; Jain, Neelu; Singh, Pradeep K.; Singh, Gyanendra Pratap; Prabhu, Kumble Vinod (Frontiers in Genetics, 2023)
Marker-assisted backcross breeding enables selective infiltration of targeted traits into the background genome to improve yield, quality and stress resistance in wheat. In the current investigation, we have transferred four drought tolerance QTLs controlling traits viz canopy temperature, NDVI, chlorophyll content, and grain yield from drought tolerant donor line C306 into a high yielding, drought stress sensitive popular variety HD2733. Marker-assisted selection coupled with stringent phenotypic selection was followed to advance each generation. This study developed 23 improved lines carrying combinations of four drought tolerance QTLs with a range of 85.35%-95.79% background recovery. The backcross-derived lines gave a higher yield under moisture deficit stress conditions in comparison to the recipient parent. They also showed higher phenotypic mean values for physiological traits and stability characters of HD2733. A promising genotype HD3411 derived from this cross was identified for release after national multilocation coordinating trials under the All India Coordinated Wheat Improvement Project. Our study is another model for precision breeding integrating markers and phenotypic selection to develop drought-tolerant cultivars.